Halal Certification in Micro, Small and Medium Enterprises (MSMEs) of the Fish Processing Industry in Sambas Regency - Muslimah, Muslimah; Kara, Muslimin H.; Masse, Rahman Ambo; Purnamasari, Wulan (Nomico, 2024)
This research departs from the phenomenon that many MSME actors in the fish processing industry sector in Sambas Regency do not register for halal certification. This study aims to identify the obstacles and problems faced by MSMEs in the Fish Processing Industry Business in Sambas Regency in obtaining Halal Certificates. This type of research is classified as qualitative with the research approach applied is field research. Data collection techniques were pursued through interviews, observation, and documentation. The results of this study indicate that the obstacles and problems faced by business actors in obtaining Halal Certificates in the fish processing industry include limited resources, inability to afford the costs required to meet halal requirements, and limited knowledge and abilities in managing production processes that meet halal standards. In addition, other problems faced are the lack of knowledge and understanding of MSME actors regarding halal certification, the low awareness and obedience of MSME actors to register halal certification, the confidence of MSME actors in the halalness of their products, and limited human resources.